1959
DOI: 10.1084/jem.109.2.197
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Transformation of Injected Colloidal Iron Complexes Into Ferritin and Hemosiderin in Experimental Animals

Abstract: Although there have been numerous studies on the fate of injected iron compounds in experimental animals (1-8), the transformation of the iron compounds within individual cells has not yet been traced at the molecular level. Recent work in which electron microscopy was combined with other techniques (9-12) has provided information on the molecular structure and the disposition of hemosiderin in several types of cells under varying circumstances, on the relationship of hemosiderin to ferritin, and on the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
58
1

Year Published

1961
1961
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 20 publications
10
58
1
Order By: Relevance
“…It had thus been determined that T. cruzi provoked a hypoferremic response, presumably by intracellular sequestration of iron within the RES (4,5). Furthermore, it was observed that iron-dextran, which preferentially delivers iron to the intracellular RES stores (13), enhanced the pathogenicity of T. cruzi infection. Hence, it was of interest to determine the effects of reduction of intracellular iron stores on the course of infection with T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had thus been determined that T. cruzi provoked a hypoferremic response, presumably by intracellular sequestration of iron within the RES (4,5). Furthermore, it was observed that iron-dextran, which preferentially delivers iron to the intracellular RES stores (13), enhanced the pathogenicity of T. cruzi infection. Hence, it was of interest to determine the effects of reduction of intracellular iron stores on the course of infection with T. cruzi.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, iron-dextran specifically produces an increase in the intracellular RES iron levels (13), whereas desferrioxamine B specifically chelates and removes intracellular iron rather than the iron bound to transferrin (14). Thus, desferrioxamine B and an iron-deficient diet protected against intracellular T. cruzi by a reduction in the intracellular iron stores, whereas iron-dextran produced a detrimental effect by augmenting intracellular iron stores.…”
Section: Introductionmentioning
confidence: 99%
“…At first individual molecules of ferritin are uniformly distributed throughout the cytoplasm, accompanied by a few molecules in the nucleoplasm but, as a rule, none in mitochondria. One week after injection, vacuoles containing a mixture of iron-dextran and ferritin are found, and these are gradually replaced by vacuoles containing only ferritin.COLLOIDAL iron preparations contain macromolecular particles which can be distinguished in electron micrographs from the images produced by the ferric hydroxide micelles of the iron-storage protein, ferritin [Richter, 1959;Bessis and Breton-Gorius, 1959;Muir, 1960]. Thus it is possible to observe the cellular transformation of administered iron preparations into ferritin and haemosiderin.…”
mentioning
confidence: 99%
“…Heavy deposition of ferritin is induced easily in animals by injecting them with and excess of iron compounds (12,19,20). Thus, the process of ferritin formation can be analyzed by using animal cells loaded with iron.…”
mentioning
confidence: 99%